PERFORMANCE APPRAISAL OF PMFBY VIS-À-VIS RWBCIS IN INDIA - S.M. KEERTHI KUMARA; D. SUJATHA SUSANNA KUMARI (The Journal of Research ANGRAU, 2020)
The study aimed to overview the numerous crop insurance schemes in India from its initial schemes to the present schemes. The study appraised the performance of “Pradhan Mantri Fasal Bhima Yojana” (PMFBY) vis-a-vis “Restructured Weather Based Crop Insurance Scheme” (RWBCIS) from 2016-17 to 2018-19.The growth rate analysis calculated to examine the number of farmers covered and the total agriculture area insured under the schemes indicated that the number of farmers covered and total agricultural area insured under PMFBY and RWBCIS was negative (-1.04% & -4.86%) and positive (1.47% & 8.22%) respectively. The Analysis of variance (ANOVA) and Multiple Least Significant Difference (LSD) tests to compare the means of farmers’ premium, gross premium, claims reported, and claims paid showed a significant difference among the parameters under both the schemes. Multiple LSD results revealed a significant difference between farmers’ premium and other parameters under both the schemes. Also,there was a significant difference between gross premium and other parameters under PMFBY only denoting that the insurance companies were more benefited under the scheme.